Biochar Addition Increases the Rates of Dissimilatory Iron Reduction and Methanogenesis in Ferrihydrite Enrichments - Zhou, Guo-Wei; Yang, Xiao-Ru; Marshall, Christopher W.; Li, Hu; Zheng, Bang-Xiao; Yan, Yu; Su, Jian-Qiang; Zhu, Yong-Guan (Frontiers in Microbiology, 2017)
Biochar contains quinones and aromatic structures that facilitate extracellular electron transfer between microbial cells and insoluble minerals. In this study, granulated biochar (1.2-2 mm) and powdered biochar (< 0.15 mm) were amended to two ferrihydrite (in situ ferrihydrite and ex situ ferrihydrite) enrichments to investigate the effect of biochar with different particle sizes on dissimilatory iron(III)-reducing bacteria (DIRB) and methanogens. Biochar addition significantly stimulated the reduction of both in situ ferrihydrite and ex situ ferrihydrite and the production of methane. Powdered biochar amendments increased iron reduction compared to granulated biochar amendment in both the in situ ferrihydrite and ex situ ferrihydrite enrichments. However, no significant difference was observed in methane production between the powdered biochar and granulated biochar amendments in the two ferrihydrite enrichments. Analysis of 16S rRNA gene sequences showed that both DIRB and methanogens were enriched after biochar amendments in the in situ ferrihydrite and ex situ ferrihydrite enrichments. Taxa belonging to the Geobacteraceae and methanogenic genus affiliated to Methanosarcina were detected with significantly higher relative abundances in powdered biochar amendments than those in granulated biochar amendments in both the ferrihydrite enrichments. X-ray diffraction analysis indicated green rust [Fe2(CO3)(OH)] and vivianite [Fe3(PO4)2. 8(H2O)] formed in the ex situ ferrihydrite and in situ ferrihydrite enrichments without biochar addition, respectively. After granulated biochar amendment, the mineral phase changed from the green rust to vivianite in the ex situ ferrihydrite enrichment, while crystalline vivianite and iron oxide (γ-Fe2O3) were detected simultaneously in the in situ ferrihydrite enrichment. No crystalline iron compound was found in the powdered biochar amendments in both ferrihydrite enrichments. Overall, our study illustrated that the addition of biochar affected iron-reducing and methane-generating microbial communities to some extent.